2013
DOI: 10.1111/papr.12148
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Diagnosed Opioid Abuse in Commercial and Medicare Managed Care Populations

Abstract: Despite a stable rate of prescription opioid use among the observed population, the prevalence of diagnosed opioid abuse is increasing, particularly in the Medicare population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 13 publications
3
56
1
Order By: Relevance
“…1–3 This epidemic has increasingly affected the elderly Medicare population, among whom rates of hospitalization for opioid overdoses quintupled from 1993 through 2012. 4–6 The risks of opioid use are particularly pronounced among the elderly, who are vulnerable to their sedating side effects, even at therapeutic doses. 7 Multiple studies have shown increased rates of falls, fractures, and death from any cause associated with opioid use in this population.…”
mentioning
confidence: 99%
“…1–3 This epidemic has increasingly affected the elderly Medicare population, among whom rates of hospitalization for opioid overdoses quintupled from 1993 through 2012. 4–6 The risks of opioid use are particularly pronounced among the elderly, who are vulnerable to their sedating side effects, even at therapeutic doses. 7 Multiple studies have shown increased rates of falls, fractures, and death from any cause associated with opioid use in this population.…”
mentioning
confidence: 99%
“…1 The population that uses Medicare, the federal insurance program for Americans who have certain disabilities or are 65 years or older, has among the highest and most rapidly growing prevalence of opioid use disorder, with more than 6 of every 1000 patients (more than 300000 of 55 million) diagnosed 2 and with hospitalizations increasing 10% per year. 3 Data on patients with commercial insurance plans (the other likely source for national population data) show just more than 1 of every 1000 patients diagnosed.…”
mentioning
confidence: 99%
“…3 Data on patients with commercial insurance plans (the other likely source for national population data) show just more than 1 of every 1000 patients diagnosed. 2 Prevention initiatives are essential for reducing the number of new patients with opioid use disorder, but treatment will be required for those already addicted to opioids. Opioid agonist therapy (OAT), including buprenorphine-naloxone (Suboxone) and methadone, is the most effective pharmacotherapy for opioid addiction.…”
mentioning
confidence: 99%
“…As federal, state, and local governments work to develop and implement policies to address the opioid crisis, targeted efforts may be needed to expand access to OUD prescribers in Medicare. This may be particularly important in areas with large numbers of dually eligible enrollees, in Southern and Midwestern regions, and in rural counties . While expanding OUD treatment is part of Centers for Medicare & Medicaid Services’ (CMS) recently issued Opioid Misuse Strategy, the specific strategies to increase access to medications in Medicare are not clear …”
Section: Discussionmentioning
confidence: 99%
“…For example, a 2014 study found that the 6‐month prevalence of OUD was 6.35 per 1000 Medicare enrollees, compared with 1.15 per 1000 patients with commercial insurance. The rate of OUD among Medicare enrollees doubled from 2008 to 2010 . A recent report estimated that in 2016 approximately 500 000 Medicare Part D beneficiaries received high amounts of opioids, defined as an average morphine equivalent dose of greater than 120 milligrams a day for at least three months.…”
Section: Introductionmentioning
confidence: 99%